Zur Aktualität der Organisationstheorie von Luxemburg und Gramsci: Zwischen emanzipatorischer Theoriebildung und ahistorischer Bezugnahme - Krug, Anne-Kathrin; Graf, Jakob (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
Big parts of the left refer to Rosa Luxemburg and Antonio Gramsci as two main theorists of organization theory. In this article, we present their thinking towards problems of class consciousness, the activity of the masses, bureaucracy, political parties, parliament and hegemony. We argue that in main regards they complement each other. Finally we figure out how one can use this theoretical approach under today’s different conditions and which problems might appear if we don’t bear in mind such differences.